The application and mechanism of Chinese medicine in the upstream treatment of atrial fibrillation - Liu, Min; Mao, Chenhan; Zhao, Fusen; Chen, Zhaoyang; Wang, Xindong (Frontiers in Cardiovascular Medicine, 2023)
Upstream treatment of atrial fibrillation (AF, for short) is a new approach to the prevention and treatment of AF with non-antiarrhythmic drugs, which is essentially primary and secondary prevention of AF. The former refers to the prevention of AF by controlling risk factors such as diabetes, hypertension, and heart failure before AF occurs, and the latter mainly refers to targeting ion channels, inflammation, oxidative stress, and other pathways to reduce or reverse atrial electrical and structural remodeling, reduction of AF load, and reduction of the chance of AF occurrence or progression. More and more studies have shown that many traditional Chinese medicines, active ingredients of Chinese medicines, and Chinese herbal formulas have definite effects on the upstream treatment of AF, but their mechanisms of action are different. Therefore, we summarized the relevant literature on the application and mechanisms of Chinese medicine on the upstream treatment of AF in recent years, hoping to be helpful for subsequent studies.